Retrospective analysis of risk factors of slide positivity among febrile patients in the Salween river valley of Shan Special Region II, northern Myanmar - Hui Liu; Jian-Wei Xu; Qi-Zhang Xu; Yi-Rou Zeng (BMC, 2018)
Abstract Background In Myanmar, epidemiological conditions have been unclear due to a lack of accurate data. In 2014 and 2016, malaria outbreaks occurred in the Shan Special Region II (SSR2). It was reported that these outbreaks were caused by malaria patients from the Salween River Valley (SRV), but further research is needed to confirm these reports. To examine the risks of malaria infection in the SSR2 section of the SRV, this paper offers a retrospective analysis based on the data we collected in 2009. Methods A multivariate logistic model was utilized to analyze risk factors associated with the slide positivity of 2009. Results of the investigation in 2009 were compared with updated data. Results The number of slide positivity was 91 (24.7%, 95% confidence interval [CI], 20.3-29.4%) among 369 people who had fever 2 weeks ago of the survey, including 74 (20.1%; 95%CI, 16.1-24.5%) cases of P. falciparum, 13 (3.5%; 95%CI, 1.9-5.9%) of P.vivax and 4 (1.1%, 95%CI, 0.3-2.8%) of P. malariae. The adjusted odds ratio (OR) was 99.8 (95% CI, 24.7-887.7) for patients' age < 15 years, 6.61 (95%CI, 3.57-10.49) for people living at an altitude of < 800 m, 6.35 (95%CI, 2.45-23.27) for people lacking knowledge on malaria transmission and knowledge on symptoms, 2.10 (95%CI, 1.22-5.11) for people taking no measures against mosquito bites and 5.55 (95%CI, 2.65-13.05) for people delaying treatment. Compared with annual parasitic incidences 13.80 per 10,000 person-years (422/305733) in 2014, 2.36 per 10,000 person-years (73/309004) in 2015 and 5.25 per 10,000 person-years (164/312310) in 2015, malaria burden is reduced. Conclusion Age, lower altitude, a lack of knowledge about malaria transmission and symptoms, inaction of measures against mosquito bites and delayed treatment-seeking were independent risk factors for slide positivity. These results indicate that malaria transmission was likely within housing settlements in the SRV, and that the transmission rates within the SRV are higher than in other areas. In order to eliminate malaria, it is important for people to obtain qualified treatment to contain artemisinin resistance. Trial registration Trial registration number: ChiCTR-COC-17012522. Retrospectively registered 31 August 2017.